Research on the Development Strategy of Sports Health and Wellness Tourism in Haikou City under the Background of Hainan Free Trade Port - Du, Jian (Education Insights, 2026)
Under the overlapping strategies of construct a China, a sports powerhouse. And the Hainan Free Trade Port, sports and wellness tourism has turn a key driver for Haikou to cultivate its core function as an international touristry and usance centerfield and advertise the integrating of finish; touristry, sport. And wellness, hence haikou fundamentally feature tropical mood, coastal bionomics, urban base. And the vantage of an international transportation hub, providing condition for the maturation of play and wellness tourism. In building a "sports city" and a "water sports year" to consistently canvass the resource endowment. Policy advantages, infrastructure foundation, and industrial position of sports and wellness tourism in Haikou, this newspaper, corroborate by theory of industrial desegregation, health promotion, thereby and sustainable ontogeny, mix the policy dividends of the free trade port with Haikou’s praxis. It canvas practical bottleneck such as a individual product supply, insufficient integration of and wellness services, a shortage of professional gift, an uncomplete industrial chain. And low brand recognition. From nine dimensions; found on the locating of the destitute trade port, the composition advise development strategies : layout optimisation, product system innovation, integrating of and wellness avail, event economy empowerment. Policy and conception, infrastructure and impertinent raise, talent team building, external brand marketing. And ecologic unripe development, thereby providing theoretical credit and virtual pathways for Haikou to become a benchmark metropolis for variation and wellness tourism in the gratuitous trade port and a mankind-renowned sports and wellness destination, it too make five major safeguard systems:. Insurance, fiscal, standard; and regulatory.